IN HOUSE TRAINING (IHT) MODEL TO IMPROVE THE ABILITIES OF ENGLISH TEACHERS IN DEVELOPING TEACHING MATERIALS - Lengkanawati, Nenden Sri; Setyarini, Sri; Sari, R. Della Kartika; Moecharam, Nicke Yunita (Universitas Pendidikan Indonesia, 2015)
The Ministerial Regulation Number 16 of the year 2007 on academic qualification standards and teacher competencies requires teachers to demonstrate four competencies: personality, social, pedagogical, and Â professional. However, there are two competencies (pedagogical and professional) which become the stumbling obstacles for teachers of English in their professional involvement. Therefore, this study was designed to aim at: (1) creating a conceptual framework for enhancing teachersâ€™ capabilities in developing and implementing teaching materials; (2) designing a model of IHT to improve the ability of teachers to develop and implement the use of teaching materials; and (3) piloting and implementing the IHT model in teacher training programs. The method used in the data analysis adopted a qualitative design with reference especially to the theory of the development of teaching materials (Crowford: 2002) and the design of IHT (Wallace: 1993). The results showed that most respondents tended to resort to the textbook as the primary source for studentsâ€™ learning activities, with some enrichment materials obtained from the Internet and other sources. Nevertheless most of the teachers were still found to encounter quite a few obstacles in developing their teaching-learning materials, appropriate to the topics as indicated in the syllabus and to the student characteristics. To alleviate this hurdle, the IHT model to be incorporated in a teacher training program could be an effective alternative to improve the ability of the teachers in developing their English teaching-learning materials.